Laser diagnostics of the mesospheric magnetic field. Understanding remote laser magnetometry in northern Norway - Serrano, Alessandra (UiT Norges arktiske universitet, 2017)
This thesis outlines initial motivations and propositions for the Mesospheric Optical Magnetometry (MOM) project, using lidar equipment at ALOMAR observatory in northern Norway to initiate a novel technique for measuring Earth’s magnetic field at approximately 90 km altitude. Included is an in-depth discussion of the physical phenomena within Earth’s mesospheric sodium layer, relevant atomic physics, and laser techniques familiar within the Laser Guide Star (LGS) community. There will be a discussion of the maximization of resonant backscatter from illuminated sodium atoms, including light polarization and optical pumping of sodium. This knowledge is then used to outline the specifications both for the current laser system located at ALOMAR and a new laser system used at Kuiper Telescope in Arizona. Finally, the LGSBloch package for Mathematica will be detailed as a tool for modeling sodium-laser interactions, and simulations of backscatter profiles for conditions at ALOMAR will be presented and discussed.